The Use of Social Media Marketing Activities to Promote a Tourism Destination: A Review - Alghamdi, Ghazi; Abdul Wahid, Nabsiah (Advances in Social Sciences Research Journal, 2024)
This study reviews the concept of SMMA in tourism context using Al-Ula, in Saudi Arabia, as an example of a tourism destination. The review focuses on ‘what’ the concept entails followed by a discussion on whether SMMA components would provide Saudi Arabia’s tourism industry with opportunities to construct a destination brand image, enhance its attractiveness, and influence tourists’ intention to visit. A systematic literature review approach is applied for this purpose. From the review, the SMMA concept is found useful for tourism marketing and entertainment, informativeness, interactivity, personalization, trendiness, and perceived institution credibility are identified as SMMA components with promotional strategy potential. SMMA can benefit Al-Ula by strengthening its brand image by promoting heritage destination activities to attract tourists’ intention to visit. The entertainment component for instance can offer tourists virtual tours of Al-Ula’s archaeological sites via engaging videos and interactive experiences. SMMA concept’s usefulness implies its importance as potential valuable promotional strategy for destinations to be shaped into favorable brand image to help increase visibility and engaging tourists towards intention to visit. Tourism operators and governments should now focus on harnessing the potential of SMMA as key to successful destination marketing in the 21st century. The study contributes to academic literature by providing a nuanced understanding of how SMMA can be strategically employed by tourism operators and governments to foster a favorable brand image, increase destination visibility, and stimulate tourist interest. It advocates for a strategic focus on exploiting the full potential of SMMA, positioning it as a cornerstone for successful destination marketing in the 21st century.